Cytogenetic evaluation of infertile men: A retrospective study - Güleç Ceylan, Gülay; Ceylan, Cavit (Turkiye Klinikleri, 2009)
Objective: Infertility was described as failure to conceive after at least 1 year of unprotected intercourse. The incidence of chromosomal abnormalities is 10 to 20 fold higher (2.2-14.3%) in males with infertility compared to the general male population (0.7-1%). In this study, we aimed to investigate the contribution of chromosomal aberrations to male infertility. Material and Methods: We analyzed male patients diagnosed with infertility referred to the Firat (Euphrates) University, Faculty of Medicine, Department of Medical Biology and Genetics within a 3-year period between 2004 and 2006 by conventional cytogenetic methods and reviewed the cytogenetic results of these patients. Results: We reviewed 94 male patients with infertility. Chromosomal abnormalities were detected in 13 (13.8%) cases and polymorphisms were present in 7 (7.4%) cases. Chromosomal abnormalities were Klinefelter syndrome (47, XXY) and 47,XYY syndrome. Polymorphisms were pericentric inversion of the chromosome 9 and Yqh polymorphisms. Conclusion: These data show that cytogenetic evaluation is necessary for an accurate approach to elucidating the causes of infertility and physicians should also be aware of the diversity of chromosomal abnormalities that play important roles in the etiology of infertility. It is clear that there are many genetic factors causing infertility such as Y chromosome microdeletions, some mutations of the CFTR gene, mutations in SOX9, KALIG1 etc., but cytogenetic examinations should be made prior to molecular studies. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Chromosome aberrations; Cytogenetics; Infertility, male